The impact of microcrystalline and nanocrystalline cellulose on the antioxidant phenolic compounds level of the cultured Artemisia absinthium - Faezeh Khosravi; Samin Mohammadi; Morteza Kosari-Nasab; Parina Asgharian (Scientific Reports, 2024)
Abstract Artemisia absinthium has long been used traditionally as an anti-microbial and antioxidant agent. Various biologically active secondary metabolites, including phenolic compounds such as gallic acid and p-coumaric acid, have been reported from the species. In addition, growing the plants under in vitro conditions enriched with elicitors is a cost-effective approach to enhance secondary metabolite production. This paper examined microcrystalline cellulose (MCC) and nanocrystalline cellulose (NCC) effects on morphological characteristics, phenolic compounds, antioxidant activity, and volatile oil content of A. absinthium. The treated shoots with various concentrations of MCC and NCC were subjected to spectrophotometric, GC–MS, and LC–MS analysis. FESEM-EDX, TEM, XRD, and DLS methods were applied to characterize MCC and NCC properties. Morphological findings revealed that the stem length, dry, and fresh weights were improved significantly (P ≤ 0.05) under several MCC and NCC concentrations. Some treatments enhanced gallic and p-coumaric acid levels in the plant. Although 1.5 g/L of MCC treatment showed the highest antioxidant activity, all NCC treatments reduced the antioxidant effect. The findings suggest that both MCC and NCC, at optimized concentrations, could be exploited as elicitors to improve the secondary metabolite production and morphological properties.